Analisis Faktor yang Mempengaruhi Ketepatan Pelaporan Keuangan Perusahaan Manufaktur 2016-2020 - Rikah Rikah (Journal Of Business, Finance, and Economics (JBFE), 2023)
This research serves to test and prove the influence of profitability, leverage, company size and company age on the accuracy of submitting financial reports. This research focuses on consumer goods industrial companies listed on the Indonesia Stock Exchange in 2016-2020 with a population of 66 companies. The sampling method was purposive sampling, so that a total sample of 38 companies was obtained. The data analysis technique used by researchers is logistic regression analysis. The research results show that profitability, leverage, company size and company age have an insignificant positive effect on the timeliness of submitting financial reports. The value of the coefficient of determination (Negalkerke R Square) is 8.5%, this shows that the influence of profitability, leverage, company size and company age is 8.5% while the remaining 91.5% is explained by factors other than the factors proposed in this research.